Alkenones as tracers of surface ocean temperature and biological pump processes on the Northwest Atlantic margin - Hwang, Jeomshik; Kim, Minkyoung; Park, JongJin; Manganini, Steven J.; Montluçon, Daniel B.; Eglinton, Timothy I. (Deep Sea Research Part I: Oceanographic Research Papers, 2014)
ISSN:0967-0637 ISSN:0198-0149